A retrospective study of the relative utility of electrophoresis in the investigation of serum proteins - Campos García, Gusdanis Alberto; Fernández Romay , Yulien; Maddela, Naga Raju; Zamora Cedeño , Aron; Talledo Pinargote , Diego; Howland Álvarez , Ivón (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundSerum protein electrophoresis (SPE) is widely used for diagnosis, management and monitoring of different immune disorders. Serum protein alterations provide valuable insights about these disorders. Electrophoresis separates proteins based on their physical properties, and the subsets of these proteins are used in interpreting the results. The purpose of this study was to analyze the results of pathological and non-pathological SPE of Ecuadorian patients. MethodsA retrospective observational study was conducted using data of pathological (871 samples) and non-pathological (752 samples) serum protein electrophoresis data of 1623 patients who attended the Gamma Clinical Laboratory of Portoviejo, province of Manabi, Ecuador. Bivariate and exploratory factorial analysis were done using following parameters: age, sex, survival, laboratory diagnosis according to electrophoretogram. ResultsThe highest frequency of deaths occurred in females (52.9%). The most frequent pathological outcomes were polyclonal hypergammaglobulinemia (49.5%), acute inflammation (21.1%), and monoclonal gammopathy (14.70%). Exploratory factorial analysis revealed that the results of pathological SPE were mainly influenced by albumin and ã-globulin fractions followed by á1-globulin, á2-globulin, and â1-globulin-â2-globulin behavior that differed from non-pathological SPE. The Kaiser-Meyer-Olkin measure was considered adequate for data analysis, and Bartlett’s test of sphericity was highly significant (p<0.001), corroborating that factor analysis is useful for the data set. ConclusionsThis evidence warrants the need for rigorous analysis of globulin concentration in SPE to avoid biased diagnosis based solely on visual inspection of patterns in the electrophoretogram. Special attention should be paid to the relationships between fractions that show the greatest influence on SPE results.